Uporaba antihistaminikov pri pospešitvi izboljšanja aken ob terapiji z izotretinoinom - Peršič, Andreja (Placebo, 2025)
The combination of isotretinoin and antihistamines in the treatment of acne shows promising results, as it improves therapeutic outcomes, reduces inflammation, and shortens the duration of treatment. Isotretinoin is an effective medication for managing severe forms of acne, while antihistamines help reduce inflammatory processes and discomfort associated with allergic reactions. Especially in patients with more severe forms of acne associated with pronounced inflammatory responses, this combination can provide an effective solution that not only improves skin condition but also contributes to greater psychological well-being. Given that acne can significantly impact quality of life, both physically and psychologically, it is important to adopt a holistic treatment approach that addresses both pharmacological and psychological aspects of care. Future research should explore the long-term effects of this combined therapy and its potential additional benefits for patients' mental health.
Keywords: acne; akne; antihistamines; antihistaminiki; combination therapy; isotretinoin; izotretinoin; kombinacija zdravljenja; Mozoljavost; Terapevtska uporaba; terapevtski izidi; therapeutic outcomes